IDENTIFIKASI FAKTOR DAN TANTANGAN DI SEKTOR PERUNGGASAN UNTUK MENINGKATKAN KELINCAHAN BISNIS DI AGROINDUSTRI INDONESIA: TINJAUAN LITERATUR - Lawrenta, Mattew; Parung, Joniarto; Wibisono, Eric (Jurnal Ilmiah Teknik Industri, 2024)
The poultry industry in Indonesia, especially the poultry sector, plays a crucial role in ensuring national food security by providing essential animal protein sources. Therefore, business agility is highly necessary to address fluctuating demand issues that can change unpredictably. Many industries in this sector have faced setbacks due to unforeseen shifts in demand. However, in implementing business agility, numerous factors need consideration, such as traditional organizational structures, bureaucratic processes that impede change, and a corporate culture resistant to transformation. This research aims to identify various challenges faced by companies in achieving business agility through a literature review using Publish or Perish software and manual searches on Google Scholar, resulting in the selection and analysis of 23 relevant journals. The findings from the literature review indicate that effective supply chain management, innovative management leadership, technological automation, adaptability to unforeseen events, investment in employee development, and a deep understanding of customer needs are key factors influencing business agility in the poultry industry in Indonesia.